Dissolution enhancement of gliclazide by preparation of inclusion complexes with β-cyclodextrin - Hiremath, S N; Raghavendra, R K; Sunil, F; Danki, L S; Rampure, M V; Swamy, P V; Bhosale, U V (Asian Journal of Pharmaceutics (AJP), 2014)
Gliclazide is an oral hypoglycemic agent used in the treatment of non-insulin-dependent diabetes mellitus. The drug is practically insoluble in water and exhibits an exceedingly slow intrinsic dissolution rate and poor bioavailability. The present study has emphasized on improving the solubility and dissolution rate of the drug by forming inclusion complex with β-cyclodextrin. Phase solubility studies indicated the formation of 1:2 M complex in solution. The value of apparent stability constant Kc was found to be 691.45 M–1. The inclusion complexes were prepared by physical mixture and kneading method. Prepared complexes were characterized by infrared (IR) spectroscopy and differential scanning calorimetry (DSC) studies, which indicated formation of 1:2 M complex. The gliclazide:β-CD (1:2 M) complex prepared by kneading method exhibited higher dissolution rate and dissolution efficiency values in 0.1-N HCl. A 20.31-fold increase in dissolution rate and 16.50-fold increase in dissolution efficiency values were observed in the kneading method. Key words: β-cyclodextrin, gliclazide, kneading method, physical mixture